SAAPIEnS: Uma Ferramenta de Autoria de Objetos de Aprendizagem e Apoio Pedagógico na Dedução Natural na Lógica Proposicional - Rodrigues, Agnaldo M.; Gluz, João Carlos (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2014)
The need of tools to help teachers, which are able to assist them in planning, implementation and monitoring of the teaching-learning process, is an important necessity in the educational area. In some cases, difficulties to access to these technologies, coupled with the lack of knowledge and understanding on the part of teachers, undermines the way in which educational contents could be developed and used. This is the main motivation behind the creation of SAAPIEnS authoring and monitoring. The tool has a multiagent system architecture built over the Heraclito system. It makes possible for teachers to create customizable learning objects for the learning domain of natural deduction in propositional logic. It also helps teachers to check and monitor how much the authored learning objects are contributing to the improvement and progress of learners.